A Psychotherapy Private Practice Social Work Practicum: Expanding Our Boundaries of Field Education Placement. Issue 1 (2nd August 2020) - Turner, George W; Derusha, Killian; Meyers, Lisa; Snyder, Ben; Gray, Amy; Asby, Michelle; Durham, Joy
Abstract: Many social workers go into private practice, providing crucial mental health services; however, there is a dearth in the scholarship outlining the social work student training for these career options. It may be argued that social work students receive little or no clinical training on how to run a private practice providing psychotherapy services. To mend this pedagogical shortcoming, a private practice field education placement is a legitimate teaching opportunity to prepare social work students to meet the mental health needs of individuals, families, and the public. Authors drew on borderlands theory described by Gloria Anzaldua as a contested space that focuses on "both and" thinking, which resonated with a sense of navigating a border filled with cultural tension between private practice and social work. Five social workers explore their unique experiences of a private practice field education placement using borderlands theory as a lens. Qualitative analysis of autoethnography narratives resulted in six themes: (1) benefits to private practice site, (2) preparation for social work, (3) private practice is social work, (4) balanced picture, (5) practicum landscape, and (6) learning opportunities. The article concludes with recommendations for social work education and research.